Complementary biomolecular coassemblies direct energy transport for cardiac photostimulators - Ze-Fan Yao; Sujeung Lim; Yuyao Kuang; Emil M. Lundqvist; Natalie Celt; Caleb O. Chung; Kathryn K. Lee; Krystal Nguyen; Lanie Le; Sheng Wei Tang; Griffin M. Milligan; Phillip Kohl; et al. (Proceedings of the National Academy of Sciences, 2025)
Charge and energy transport within living systems are fundamental processes that enable the autonomous function of excitable cells and tissues. To date, localized control of these transport processes has been enabled by genetic modification approaches to render light sensitivity to cells. Here, we present peptidic nanoassemblies as constituents of a cardiac biomaterial platform that leverages complementary sequence interactions to direct photoinduced energy transport at the cellular interface. Photophysical characterizations and conductivity measurements confirm the occurrence of energy/charge transfer and photocurrent generation upon optical excitation in both dry and electrolytic environments. Comparing an electrostatic sequence pair against a sequence-matched donor–acceptor coassembly, we demonstrate that the sequence design with charge complementarity shows more prominent photocurrent behavior. With the flanking bioadhesive units, the primary and stem cell–derived cardiomyocytes interfaced with covalently stabilized films of the optoelectronic nanostructures exhibited material-stimulated genotypic, structural, or functional cardiac features. Collectively, our findings introduce an optoelectronic cardiac biomaterial where coassembled peptide nanostructures are molecularly designed to induce light sensitivity in excitable cells without gene modification, influencing in vitro cardiac contractile behavior and expression of cardiac markers.